Mitochondrial ascorbic acid is responsible for enhanced susceptibility of U937 cells to the toxic effects of peroxynitrite. (16th September 2013) - Guidarelli, Andrea; Cerioni, Liana; Fiorani, Mara; Azzolini, Catia; Cantoni, Orazio
Summary Otherwise nontoxic levels of peroxynitrite promote toxicity in U937 cells pre‐exposed to low micromolar concentrations of l‐ascorbic acid (AA). This event was associated with the mitochondrial accumulation of the vitamin and with the early formation of secondary reactive oxygen species and DNA single‐strand breaks. The same concentrations of peroxynitrite, however, failed to elicit detectable effects in cells pre‐exposed to dehydroascorbic acid (DHA), in which mitochondrial accumulation of vitamin C did not occur despite the identical cytosolic levels. Coherently, oxidation of extracellular AA failed to affect the intracellular concentration of the vitamin, but nevertheless prevented its mitochondrial localization as well as the enhanced response to peroxynitrite. Furthermore, in cells postincubated in vitamin C‐free medium, time‐dependent loss of mitochondrial AA was paralleled by a progressive decline of susceptibility to peroxynitrite, under the same conditions in which cells retained about half of the initial AA. Using different experimental approaches, we finally showed that the enhancing effects of AA are mediated by events associated with peroxynitrite‐dependent superoxide/H2O2 formation in the mitochondrial respiratory chain. Collectively, these results indicate that mitochondria actively take up vitamin C as AA and respond to otherwise inactive concentrations of peroxynitrite with the mitochondrial formation of secondary species responsible for DNA damage and toxicity. DHA preloading, while leading to the accumulation of identical levels of vitamin C, fails to produce these effects because of the poor mitochondrial accumulation of the vitamin © 2013 BioFactors, 40(2):236–246, 2014